Young Sun troopers - Ang, Jade Zhi Hui (2015)
This paper presents Young Sun Troopers, a health communications campaign by four final year undergraduates at Wee Kim Wee School of Communication and Information (WKWSCI) in Nanyang Technological University (NTU). Local skin cancer rates rose by an alarming 60% in the last decade (National Skin Centre, 2014). Dermatologist Dr. Wong Su-Ni verified that one blistering childhood sunburn doubles the risk of melanoma, a form of malignant skin cancer, in adulthood. Skin cancer is preventable, yet health agencies and the media had not shown urgency in addressing the problem. The team’s formative survey amongst 213 Singaporean parents found that nine in ten do not practise regular sun protection for their children during outdoor activities. Knowledge on irreversible sun damage is also severely inadequate. Prompted by this worrying situation, the team designed their campaign to educate parents on the importance of sun protection, and motivate them to inculcate sun-safe habits in their children.Informed by findings, the team employed a strategic communication plan to Rationalise, Persuade, and Incentivise, with the goal to convert knowledge into behavioural intent. To disseminate credible messages, they partnered with healthcare institutions, including National University Hospital (NUH) and KK Women’s and Children’s Hospital (KKH). At parks and SAFRA Clubhouses, they educated parents in the relevant context of outdoor play for sun-safe behaviours. The campaign also targeted children aged 7 to 12 through school-based intervention, so as to complement parent outreach initiatives. This strategy encouraged sustainable habits through mutual parent-child influence. Assessment of these efforts showed significant positive impact on knowledge and behavioural intent, for parents and children.